2014
DOI: 10.1177/216507991406200703
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict, Psychological Distress, and Sleep Deficiency among Patient Care Workers

Abstract: Objectives-There is a well-established link between psychological distress, work-related stress and sleep. The aim of this study was to test the hypothesis that work-family conflict was associated with sleep deficiency both cross-sectionally and longitudinally while controlling for potential covariates.Methods-In this two-phase study, a workplace health survey was collected from a cohort of patient care workers (n=1,572) at two large hospitals. Follow-up was collected nearly two years later in a subsample (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
(105 reference statements)
2
23
0
1
Order By: Relevance
“…39 CDC analyses of 2010 National Health Interview Survey data revealed that 30.0% of employed US civilian adults report short sleep duration (≤6 hours/day), with significant variation by sector. 73 Healthy People 2020 articulates a federal goal of increasing the proportion of Americans receiving adequate sleep by 1%, 11 an uphill battle in the face of increasing short sleep among employed US adults. 74 The full mediation of the intervention effect on sleep sufficiency via reductions in control over work hours and work-family conflict suggests that we should also expect other generalized benefits of reduced work stress for employees and employers, such as improved health and reduced absenteeism/turnover.…”
Section: Discussionmentioning
confidence: 99%
“…39 CDC analyses of 2010 National Health Interview Survey data revealed that 30.0% of employed US civilian adults report short sleep duration (≤6 hours/day), with significant variation by sector. 73 Healthy People 2020 articulates a federal goal of increasing the proportion of Americans receiving adequate sleep by 1%, 11 an uphill battle in the face of increasing short sleep among employed US adults. 74 The full mediation of the intervention effect on sleep sufficiency via reductions in control over work hours and work-family conflict suggests that we should also expect other generalized benefits of reduced work stress for employees and employers, such as improved health and reduced absenteeism/turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Conflict between work and family is associated with lower quality [3739] and quantity [38] of sleep. These effects are largest when work and family demands are highest [40] and tend to persist: high work-family conflict is associated with higher frequency of insufficient sleep 2 years later [39].…”
Section: Family Structure Household Factors and Sleepmentioning
confidence: 99%
“…These effects are largest when work and family demands are highest [40] and tend to persist: high work-family conflict is associated with higher frequency of insufficient sleep 2 years later [39]. There is compelling evidence that this relationship may be causal; a randomized-controlled workplace intervention to reduce work-family conflict increased actigraphy-assessed sleep duration and reduces self-reported sleep insufficiency 1 year later as compared to a control group [41].…”
Section: Family Structure Household Factors and Sleepmentioning
confidence: 99%
“…In addition to the sleep problems that impact most shift workers, nurses often have family responsibilities such as child and/or elder care that interfere with daytime sleep. Sleep disturbances have been reported as a possible consequence of work‐family conflict in patient care workers (Jacobsen et al., ) and other occupational groups (Aazami, Mozafari, Shamsuddin, & Akmal, ; Lallukka et al., ).…”
Section: Introductionmentioning
confidence: 99%